Cosmetic and Therapeutic Applications of Fish Oil’s Fatty Acids on the Skin - Huang, Tse-Hung; Wang, Pei-Wen; Yang, Shih-Chun; Chou, Wei-Ling; Fang, Jia-You (Marine drugs, 2018)
Fish oil has been broadly reported as a potential supplement to ameliorate the severity of some skin disorders such as photoaging, skin cancer, allergy, dermatitis, cutaneous wounds, and melanogenesis. There has been increasing interest in the relationship of fish oil with skin protection and homeostasis, especially with respect to the omega-3 polyunsaturated fatty acids (PUFAs), docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA). The other PUFAs, such as α-linolenic acid (ALA) and linoleic acid (LA), also show a beneficial effect on the skin. The major mechanisms of PUFAs for attenuating cutaneous inflammation are the competition with the inflammatory arachidonic acid and the inhibition of proinflammatory eicosanoid production. On the other hand, PUFAs in fish oil can be the regulators that affect the synthesis and activity of cytokines for promoting wound healing. A systemic review was conducted to demonstrate the association between fish oil supplementation and the benefits to the skin. The following describes the different cosmetic and therapeutic approaches using fatty acids derived from fish oil, especially ALA, LA, DHA, and EPA. This review summarizes the cutaneous application of fish oil and the related fatty acids in the cell-based, animal-based, and clinical models. The research data relating to fish oil treatment of skin disorders suggest a way forward for generating advances in cosmetic and dermatological uses.